2003
DOI: 10.1172/jci200315524
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma phenylacetic acid in patients with end-stage renal failure inhibits iNOS expression

Abstract: NO prevents atherogenesis and inflammation in vessel walls by inhibition of cell proliferation and cytokine-induced endothelial expression of adhesion molecules and proinflammatory cytokines. Reduced NO production due to inhibition of either eNOS or iNOS may therefore reinforce atherosclerosis. Patients with end-stage renal failure show markedly increased mortality due to atherosclerosis. In the present study we tested the hypothesis that uremic toxins are responsible for reduced iNOS expression. LPS-induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…The significant increase in LOX-1 expression in the above in vitro studies suggests that elevated plasma levels of this natural eNOS inhibitor, ADMA, found in patients with chronic renal failure and in hypercholesterolemia, may play a pathophysiological role in the development of endothelial dysfunction and early atherosclerosis. Interestingly, it has recently been found that the phenylacetic acid (PAA), a degradation product of phenylalanine, another potent inhibitor of NOS, also accumulates in patients with end-stage renal disease (19). In healthy subjects, PAA was not detectable in plasma, whereas in patients with end-stage renal failure, plasma concentrations of PAA were 3.49 Ϯ 0.33 mmol/l (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant increase in LOX-1 expression in the above in vitro studies suggests that elevated plasma levels of this natural eNOS inhibitor, ADMA, found in patients with chronic renal failure and in hypercholesterolemia, may play a pathophysiological role in the development of endothelial dysfunction and early atherosclerosis. Interestingly, it has recently been found that the phenylacetic acid (PAA), a degradation product of phenylalanine, another potent inhibitor of NOS, also accumulates in patients with end-stage renal disease (19). In healthy subjects, PAA was not detectable in plasma, whereas in patients with end-stage renal failure, plasma concentrations of PAA were 3.49 Ϯ 0.33 mmol/l (19).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has recently been found that the phenylacetic acid (PAA), a degradation product of phenylalanine, another potent inhibitor of NOS, also accumulates in patients with end-stage renal disease (19). In healthy subjects, PAA was not detectable in plasma, whereas in patients with end-stage renal failure, plasma concentrations of PAA were 3.49 Ϯ 0.33 mmol/l (19). According to Sydow et al (46), ADMA inhibits the conversion of L-(guanidino-15 N 2 )arginine to 15 N-nitrite (a specific index of NOS activity) at concentrations of Ն5 M in human endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Molar concentrations ranged from a few picomoles per liter for ILs to micromoles per liter for phenylacetic acid. 22,31 The highest mass concentration was detected for the acute phase macromolecule a1-acid glycoprotein. 54 Most frequently reported concentrations concerned b2-microglobulin, indoxyl sulfate, homocysteine, uric acid, and parathyroid hormone (PTH).…”
Section: Overview Of Uremic Toxin Researchmentioning
confidence: 99%
“…Phenylacetic acid, also a protein-bound retention solute, inhibits iNOS expression in a dosage-dependent manner. 25 Inhibition of either endogenous NOS or iNOS may reinforce vascular damage. Furthermore, phenylacetic acid inhibits Ca 2ϩ -ATPase activity, increasing intracellular Ca 2ϩ concentrations.…”
Section: Leukocytesmentioning
confidence: 99%